Estado del arte de la quinua en el mundo en 2013: Perú - Gómez Pando, L.; Mujica, Ángel; Chura Parisaca, Eusebio; Canahua, A.; Perez Avila, Angel Agustin; Tejada Campos, Toribio Nolberto; Villantoy Palomino, Abraham; Pocco, M.; Gonzales, V.; Marca, S.; Ccoñas, W. (PE, 2022)
12 páginas